THE POTENTIAL GRAM-NEGATIVE ENDOPHYTIC BACTERIA FROM PEGAGAN (Centella asiatica) WITH QUORUM-QUENCHING ACTIVITY - Nur Al Huda; Mahyarudin Mahyarudin; Mitra Handini; Ambar Rialita; Mardhia Mardhia (Majalah Kedokteran Andalas, 2020)
Background: Quorum-sensing is communication between bacterial involved in virulence. Bacterial virulence can be inhibited by quorum-quenching mechanism. Endophytic bacteria of pegagan leaf may produce secondary metabolit similar to bioactive compounds in the leaf wich can act in quorum-quenching; Aims: The study aimed to determine quorum-quenching ability in gram-negative bacteria from pegagan leaf; Methods: Gram-negative endophytic bacteria from pegagan were isolated, purified and subcultured by streak plate method on Nutrient Agar. Quorum-quenching activity was evaluated  by measuring the purple color inhibition zone of C. violaceum. Five Bacteria with the largest inhibition zones were characterized based on the characteristics of colony morphology, cell morphology and biochemical activities; Results: A total of 15 pure isolates of Gram-negative endophytic bacteria were obtained from 46 pure isolates of endophytic bacteria from Centella asiatica leaves. All isolates of Gram-negative endophytic bacteria showed quorum-quenching activity with inhibitory zones ranged from 9.0 to 13.0 mm. Five isolates that showed the largest quorum-quenching activity were included in genus Flavimonas, Flavobacterium and Acinetobacter; Conclusions: Gram-negative endophytic bacteria from pegagan leaf (Centella asiatica) potential to have quorum-quenching activity against Chromobacterium violaceum.